The Relationship between Spiritual Needs and Anxiety Levels in the Elderly Adults Who Do Not Have a Spouse in the Village of Kapannan Cirebon Regency - Wahyuni, Yeni; Sutarna, Agus (Indo Consultan Energi, 2023)
Spiritual needs with anxiety levels in the elderly who do not have a life partner are based on the fulfilment of individual spiritual needs. It is done differently based on age, gender, culture, and religion. This study aimed to determine the relationship between spiritual needs and anxiety levels in the elderly who do not have a life partner in Kapanan Village, Depok District, Cirebon Regency, in 2022. This study used a quantitative method with a cross-sectional approach. A sample of 82 respondents was taken from the entire population of older adults and women who did not have a partner. The sample was selected based on purposive sampling through questionnaires and interviews. Data were analyzed using chi-square statistics. The study found that 58 people had moderate spiritual needs, with an anxiety level of 34.1% and severe anxiety of 36.6%. The study's results found a relationship between spiritual needs and anxiety in the elderly who do not have a life partner in Secondna Village, Depok District, Cirebon Regency, in 2022. For older adults who do not have a partner who needs spiritual care, controlling their anxiety can be done by providing motivational activities and religious activities following their respective beliefs